Oil price transmission, deficit financing and capital formation - Ebi, Bassey Okon; Aladejare, Samson Adeniyi (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study investigated the magnitude of the transmission effect from oil price, to deficit financing, and capital formation using the Generalised Method of Moment approach. Based on the Nigerian data, the findings reveals a significant but small inverse oil price transmission effect, through the oil revenue channel to deficit financing. This indicates that growth in public spending is currently pacing faster than government revenue, due to poor fiscal management. In contrast, the transmission effect from oil price, through the oil revenue and deficit financing channels, to capital formation is significantly positive but minute in magnitude. The weak response of capital formation to the transmission effect from oil price, is due to the increasing use of oil proceeds in funding government’s recurrent outlays over the years. Hence, channelling positive growth in oil prices, and repositioning the use of deficit financing to growing capital formation as against consumption demands, will increase diversification of government revenue base and investors’ confidence in the economy through growth in FDI inflows.